Cold applications for recovery in adolescent athletes: a systematic review and meta analysis - Murray, A.; Cardinale, M. (Extreme Physiology & Medicine, 2015)
Recovery and regeneration modalities have been developed empirically over the years to help and support training programmes aimed at maximizing athletic performance. Professional athletes undergo numerous training sessions, characterized by differing modalities of varying volumes and intensities, with the aim of physiological adaptation leading to improved performance. Scientific support to athletes focuses on improving the chances of a training programme producing the largest adaptive response. In competition it is mainly targeted at maximizing the chances of optimal performance and recovery when high performance levels are required repeatedly in quick succession (e.g. heats/finals). In recent years, a lot of emphasis has been put on recovery modalities. In particular, emphasis has been placed on the need to reduce the delayed onset of muscle soreness (DOMS) typically evident following training and competitive activities inducing a certain degree of muscle damage. One of the most used recovery modalities consists of cold-water immersion and/or ice/cold applications to muscles affected by DOMS. While the scientific literature has provided a rationale for such modalities to reduce pain in athletes and recreationally active adults, it is doubtful if this rationale is appropriate to aid training with adolescent athletes. In particular, since these methods have been suggested to potentially impair the muscle remodeling process leading to muscle hypertrophy. While this debate is still active in the literature, many coaches adopt such practices in youth populations, simply transferring what they see in elite sportspeople directly; without questioning the rationale, safety or effectiveness as well as the potential for such activity to reduce the adaptive potential of skeletal muscle remodeling in adolescent athletes. The aim of this review was to assess the current knowledge base on the use of ice/cold applications for recovery purposes in adolescent athletes in order to provide useful guidelines for sports scientists, medical practitioners, physiotherapists and coaches working with such populations as well as developing research questions for further research activities in this area. Based on the current evidence, it seems clear that evidence for acute benefits of such interventions are scarce and more work is needed to ascertain the physiological implications on a pre or peri-pubertal population.